Tools for Assessing the Costs and Benefits of Green Growth : The U.S. and Mexico - Harrington, Winston; Morgenstern, Richard; Velez-Lopez, Daniel (World Bank, Washington, DC, 2013)
This paper examines the processes used in the United States and Mexico to assess the economic costs and benefits of environmental improvement, the kinds of information obtained from these procedures, and the additional knowledge that is needed about both elements to improve understanding of the problems and prospects of advancing a green growth agenda. Because environmental and other development needs are large and resources are limited, it is important to choose the best projects, those with the highest returns on both public investments and private resources harnessed by regulation. The United States is well-established as a world leader in the use of quantitative methods to evaluate options for environmental regulation and policy. Mexico represents a case where a developing country has made clear advances in reforming its economy and in introducing transparency in its regulatory processes for environmental and other policy areas.